O desenvolvimento territorial urbano e sua transformação geoespacial entre os anos de 2000 e 2020 no município de Campinas - SP - Azevedo, Guilherme Sarausa de (Universidade Federal de São Carlos, 2021)
The growth history of the city of Campinas contains many of the elements of the colonial city, an important center of sugar and later coffee production in the interior of São Paulo. However, it is from the process of industrialization and the migration of millions of workers from the countryside to the city, including Campinas, from the 1930s onwards, that there is a considerable growth in the urban area of the city. This growth was accentuated between the 1950s and 1970s, with the intensification of industrialization in Brazil, and a subsequent process of industrial deconcentration in São Paulo, which has the Campinas region as one of its main destinations. The urban growth of Campinas contains the contradictions of an industrialization process that took place with low wages and precarious jobs. It is a city that grew in a fragmented and often irregular way, largely as a result of the production of housing for the lower classes. After this period, the last decades of the last century had a much lower urban growth, mainly as a result of economic crises, which cooled and reversed the previous process of industrialization and, consequently, the population's attractiveness. This dissertation seeks to analyze how the expansion of the Urban Spot in the city of Campinas took place, between 2000 and 2020, through the production of thematic maps. Using a Geographic Information System (GIS), a documental and qualitative analysis of the city's urban growth was carried out. Thus, the mechanics of dispersed urban growth were verified in Campinas, with some occupations of previously existing urban voids, mainly from large commercial projects or closed residential projects (closed condominiums and subdivisions), but still with the emergence of New Spots Fragmented urban areas. With the alteration of the Urban Perimeter in 2018, and the transformation of almost the entire rural area of the municipality into an area of urban expansion, there is a tendency for the process of fragmentation and dispersion of the city's growth to strengthen in the next period
Urban territorial development and its geospatial transformation between 2000 and 2020 in the city of Campinas - SP
Keywords: Mancha urbana; Crescimento urbano; Urbanização de Campinas; Análise espacial; Urbanização; Urban spot; Urban growth; Urbanization of Campinas; Spatial analysis; Urbanization; ENGENHARIAS